2021
DOI: 10.1021/acsaem.1c01045
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Thermoelectric Transport Properties of n-Type PbS Induced by Adding Ni and Zn

Abstract: Introducing small metallic atoms is an effective approach to enhance thermoelectric performance. In this research, we investigate the impacts of Ni and Zn on the thermoelectric performance of n-type PbS. We find that adding Ni is superior to that of Zn. Both experimental and theoretical results show that the extra Ni could bring a new impurity level among the Fermi energy, thus the electrons can be easily excited from defect states, leading to enhanced carrier mobility. Above all, adding Ni can boost the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…3b . Comparing the κ lat of our PbS 0.6 Se 0.4 sample with other reported lead chalcogenide materials, the PbS 0.6 Se 0.4 shows a relatively low κ lat , especially at room temperature 37 , 42 44 , 46 49 (Supplementary Fig. 3c ).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…3b . Comparing the κ lat of our PbS 0.6 Se 0.4 sample with other reported lead chalcogenide materials, the PbS 0.6 Se 0.4 shows a relatively low κ lat , especially at room temperature 37 , 42 44 , 46 49 (Supplementary Fig. 3c ).…”
Section: Resultssupporting
confidence: 51%
“…Finally, because of the improvement in TE performance at room temperature, the ZT ave of our sample reaches ~0.92 at the temperature range of 300-823 K, as depicted in Fig. 5f, which is the highest ZT ave among PbS-based material systems 21,[37][38][39][40][41][42][43][44][45][46] .…”
Section: Growing Crystal To Improve the Carrier Mobility And Thermoel...mentioning
confidence: 87%
See 1 more Smart Citation
“…[11][12][13] It is reported that the strategy of interstitial doping in thermoelectric materials can synergistically optimize electrical and thermal transport properties and even decouple the carrier and phonon transport due to their large different mean free paths. 14,15 In PbQ (Q = Te, Se and S) compounds, Zn, 16,17 Ni, 17,18 Cu [19][20][21] and Ag 22 atoms can form interstitials in the matrix lattice. These sub-nanoscale interstitials could intensify the phonon scattering to decrease lattice thermal conductivity due to the comparable size with the phonon mean free path, while simultaneously maintaining carrier transport because of a much larger carrier mean free path.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the strategy of interstitial doping in thermoelectric material can synergistically optimize electrical and thermal transport properties, and even decouple the carrier and phonon transport due to large difference in mean free paths. 19,20 In PbQ (Q = Te, Se and S) compounds, Zn, 21,22 Ni, 22,23 Cu [23][24][25][26] and Ag 27 atoms can form interstitials in matrix lattice. These sub-nanoscale interstitials could intensify the phonon scattering to decrease lattice thermal conductivity due to the comparable size with phonon mean free path, while simultaneously maintaining carrier transport because of much larger carrier mean free path.…”
Section: Introductionmentioning
confidence: 99%